DESAIN PENGEMBANGAN JARINGAN TRANSPORTASI PENYEBERANGAN UNTUK MENDUKUNG DISTRIBUSI GENERAL CARGO ANTAR-PULAU DI PROVINSI MALUKU - Hanok Mandaku; Mentari Rasyid (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
Ferry transport plays an important role in the general cargo distribution process in the Maluku region. However, the network pattern that has been applied has not been effective so that the area in the southern part is still isolated because the frequency of ship stops is more than two weeks. This condition impedes the distribution of general cargo, increases logistics costs and reduces industrial competitiveness. The purpose of this research is to evaluate and develop an optimal crossing transport network through simulating the distance and shipping time. The results showed that the existing pattern requires 109.05 hours of travel time to reach 2,103 km as the farthest distance. The scenario for developing the multiport calling pattern requires 1 ship to sail the primary route, covering the farthest distance of 3,442 km in 178.27 hours. Scenario I hub and spoke pattern requires 2 ships to sail the primary route, covering the farthest distance of 1,872 km in 96.96 hours. Scenarios II and III require 3 ships to sail the primary route, covering the farthest distance of 2,336 km in 120.99 hours. These results confirm that the hub and spoke pattern is more optimal than the multiport calling pattern even though it requires more ship units. Thus, the hub and spoke scenario III pattern is more appropriate to be applied as an inter island crossing transport network pattern in the Maluku region because it is able to reach all areas so that it can support the distribution of general cargo.